Effects of pollutants in the Ria Formosa Lagoon, Portugal - Bebianno, Maria João (2020)
The Ria Formosa is a most significant area from the point of view of fisheries, particularly with respect to the culture of molluscean shellfish. Eighty percent of the bivalves (e.g. cross-cut carpet shell, Venerupis decussata) harvested in Portugal come from this area. There are in this coastal lagoon rapidly increasing levels of anthropogenic releases of contaminants transported by untreated sewage and industrial and agriculture effluents. High levels of bacteria, nutrients, metals and organochlorine compounds were detected in the water column as well as suspended solids and sediments in several areas of the lagoon, mainly in the areas surrounding the main cities. Some of these pollutants have been accumulating in the tissues of several bivalve species. The accumulation of these pollutants along with the increase in temperature over the summer resulted in deleterious effects on these species some of which became unsafe for human consumption. These anthropogenic releases together with an ineffective clam harvest practice resulted in a massive clam mortality. This mortality generally occurs after summer and bivalve production has shown a significant decrease in the past 5 years with a negative impact on the economy of the region. Along with held experiments, laboratory studies have been carried out to investigate the biological effects of sublethal concentrations of some of these pollutants in the most commercially important species harvested in the region